Doctrine of laches and its application in actions founded on contract in Malaysia - Md Dahlan, Nuarrual Hilal (Lexisnexis Malaysia Sdn. Bhd, 2002)
In a remedial contractual action, the limitation period plays an important part before one commences an action against the defaulting party to a contract. The provision of a limitation period to enforce a contract is found in s 6 of the Limitation Act 1953 ('the Act'). By virtue of this provision, one has to commence remedial action either in the form of specific performance or damages within six years from the date of accrual of the cause of action, failing which his action is deemed to have failed and shall be struck out by the court. Apart from this, at common law and in statutory footing under the Malaysian Limitation Act 1953 (Act 254), there is another equitable doctrine that could affect the plaintiffs action. This doctrine is called the doctrine of laches. In short, this doctrine states that if the plaintiff commences an action with unreasonable delay (laches) after the accrual of the cause of action, his action will be defeated.